Complex Dietary Topologies in Non-alcoholic Fatty Liver Disease: A Network Science Analysis - Xia, Yang; Zhao, Zhiying; Zhang, Shunming; Liu, Yashu; Meng, Ge; Zhang, Qing; Liu, Li; Wu, Hongmei; Gu, Yeqing; Wang, Yawen; Zhang, Tingjing; Wang, Xing; et al. (Frontiers in Nutrition, 2020)
Background and Aims: Previous studies have explored the associations between nutrition (food groups, nutrients, and dietary patterns) and the prevalence of non-alcoholic fatty liver disease. However, it remains unclear whether how foods are consumed together is associated with non-alcoholic fatty liver disease. The present study aims to construct dietary networks from network science and to explore the associations between complex dietary networks and non-alcoholic fatty liver disease. Methods: The present case–control study generated 2,043 multivariate matched controls for 2,043 newly diagnosed non-alcoholic fatty liver disease cases. Mutual information, which represents both linear and nonlinear dependencies among food groups, was used to construct the network topologies. Results: The dietary topologies in the studied case and control groups were different despite the fact that only few food groups show differences in absolute intake. The dietary structure of the case group focused on two major components with more cohesion among food groups, while contrarily the control group had one major component with higher diversity of food groups. The dietary topology of the case group showed equality in connections among beneficial and detrimental food groups, whereas the control group focused more on healthier food choices. Conclusions: This study suggests how foods are consumed, besides the absolute intake, could be an important determinant of the occurrence of non-alcoholic fatty liver disease. A diverse diet that focuses on whole grain, tubers, and vegetables could yield beneficial effects regarding non-alcoholic fatty liver disease. Network science could offer a complementary tool in nutritional epidemiology.